Human rights and sustainability in free trade agreements: Can the Cariforum-EU Economic Partnership Agreement serve as a model? - Evita Schmieg (Stiftung Wissenschaft und Politik (SWP), 2014)
The liberalisation of foreign trade has often contributed to stimulating development and increasing prosperity. But it can also lead to unemployment, environmental problems and threats to food security. Free trade agreements should therefore be designed to ensure that positive effects are felt quickly, and provisions should be made for dealing with negative effects. In recent years the European Union and the United States have already concluded free trade agreements containing clauses on sustainability and human rights backed up with instruments for impact assessment and monitoring. The European Union's Economic Partnership Agreement with Cariforum contains formulations that could serve as a model in this respect. (SWP Comments)
Keywords: 320